Enhancement of quality factor in ST-cut quartz surface acoustic wave devices by using different numbers of IDTs and wavelengths for gas sensing - Md Ralib @ Md Raghib, Aliza 'Aini; Mohamad Razali, Nur Fatin; Chatras, Matthieu; Nordin, Anis Nurashikin; Abdul Rahman, Farah Diyana; Pothier, Arnaud; Passerieux, Damien; Guines, Cyril (IEEE, 2023)
A robust sensing mechanism requires a high sensitivity, fast response, and good fabrication compatibility. A surface acoustic wave (SAW) device possesses such properties, which make it suitable for gas sensing. This paper reported on the design, fabrication, characterization and measurement of a two-port SAW device built on an ST-cut quartz piezoelectric substrate. In order to develop a reliable SAW device, some performance parameters should be considered, such as the quality factor and electromechanical coupling coefficient. There are several possible ways to increase the quality factor of a SAW device such as by varying the number of interdigitated electrode (IDT) pairs as well as by using different IDT wavelengths. The devices were fabricated using three different numbers of IDTs (N=24,48 , and 72) and two different IDT wavelengths (λ=20 μm and 80 μm) . The calculated quality factor, Q, confirmed that increasing the number of IDTs and reducing the value of the IDT wavelength would lead to a higher quality factor. The optimized SAW device with 72 IDTs and an IDT wavelength of 20 μm showed the highest quality factor of 306.58 at a resonance frequency of 248.33 MHz. The results of this study suggest that the ST-cut quartz SAW device with a high number of IDTs and small wavelength can be a better candidate for a surface acoustic wave device for sensing applications such as gas sensing.